INFORMATION STRUCTURE IN EFL TEACHING - Gültekin Boran (Informascope, 2015)
When speaking or writing in a foreign language, being grammatically and semantically competent may not be enough to convey the necessary information to the interlocutors in dual conversations or to the readers who read our texts in various genres such as personal letters, formal letters, e-mails...etc., Namely, individuals who use a foreign language in their communications may generate grammatically and semantically well formed sentences or phrases but their sentences and phrases may still not be comprehensible because they fail in highlighting the new information and deemphasizing the old information. Therefore, teaching intonation, sentence stress and pitch as important characteristics of spoken language and teaching how to highlight new information and deemphasise old information when writing a text are of great importance in foreign language teaching. In this article, the concept of information structure is reviewed, examples are given both in Turkish and English and suggestions are made for EFL (English as a Foreign Language) classes.   Key Words: information structure, pragmatics, teaching pronunciation